ADMINISTRATION OF FASAKH JUDGMENTS IN THE DISSOLUTION OF MUSLIM MARRIAGES IN INDONESIA AND MALAYSIA: A COMPARATIVE STUDY OF LEGAL BASES, REGISTRATION PROCEDURES, AND THE ISSUANCE OF DIVORCE DOCUMENTS - Deris Arista Saputra; Zul-kifli Hussin (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyse the administration of fasakh judgments in the dissolution of Muslim marriages in Indonesia and Malaysia, with specific attention to the legal bases, registration procedures, and issuance of divorce documents. This issue is significant because the dissolution of marriage does not end with a court judgment. It continues through administrative registration, which determines the legal status of the parties after divorce. This study adopts a qualitative approach with a documentation-based comparative case study design. Data were collected through an examination of statutory regulations, judicial technical guidelines, official service procedures, institutional documents, and administrative information applicable to the Religious Courts in Indonesia, as well as the Syariah Courts and State Islamic Religious Departments in Malaysia. This study does not involve interviews or participants because its focus is directed toward the objective mapping of applicable administrative procedures. The data were analysed using a comparative thematic approach by grouping the findings into three main themes: the legal basis of judicial authority, post-judgment registration procedures, and the forms of divorce documents issued. The findings show that Indonesia integrates the issuance of divorce certificates into the administration of the Religious Courts, whereas Malaysia places the issuance of Islamic divorce certificates within the institutional relationship between the Syariah Courts and the State Islamic Religious Departments. These findings affirm that fasakh is not merely a juristic concept or a ground for marital dissolution, but also forms part of the legal documentation system of Islamic family law. This study contributes to the development of comparative Islamic family law scholarship and provides a basis for mapping Muslim divorce administration policies in both countries.